The development of pupils’ written speech by the means of interactive teaching (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article presents the specialities of developing process of the written speech as a kind of speech activity. This process demands the motivating support, creating the atmosphere of intellectual interaction by using the interactive methods of teaching. The author motivates the need of correlating between selecting the interactive strategies and stages of work on the pupils’ written speech.
Keywords: written speech; motivation; interactive teaching; interactive strategies